Changes in the number and causes of maternal deaths after the introduction of pregnancy checkbox on the death certificate in Taiwan - Ching-Yi Lin; Pei-Yin Tsai; Liang-Yi Wang; Ginden Chen; Pao-Lin Kuo; Meng-Chih Lee; Tsung-Hueh Lu (Elsevier, 2019)
Objective: To examine changes in the number and causes of maternal deaths after the introduction of pregnancy checkbox on the death certificate in January 2014 in Taiwan. Materials and methods: We first used the cause-of-death (COD) mortality data for years 2010 through 2017 to examine the number of deaths by item of pregnancy checkbox. We then compared the distribution of the causes of maternal deaths before and after the introduction of pregnancy checkbox. Results: Between 2014 and 2017, 111 women died, for whom the certifiers indicated the following in the pregnancy checkbox items: 2 (pregnant at the time of death; n = 10), 3 (died within 42 days after the termination of pregnancy; n = 64), and 4 (died between 43 days and 1 year after the termination of pregnancy; n = 37). However, in only 61 of the 111 deaths, the certifiers reported pregnancy or delivery-related diagnosis in the COD section of the death certificate-5 each for items 2 and 4 and 51 for item 3. The number of maternal deaths was 55 in 2010-2013; this number increased to 82 in 2014-2017. A decline in the percentage of maternal deaths from obstetric hemorrhage was noted from 38% (21/55) in 2010-2013 to 21% (17/82) in 2014-2017. Conclusion: The number of maternal deaths increased, and the distribution of causes of maternal deaths changed after the introduction of pregnancy checkbox. Additional studies are required to examine the possible misclassification of pregnancy-associated deaths indicated in the pregnancy checkbox. Keywords: Cause-of-death, Death certificate, Pregnancy checkbox, Pregnancy-associated deaths, Maternal deaths